2HD Analysis of Morphologic Responses to the Tsunami Impacts Using Process-based Model. (2015) - Son, Sangyoung; Jung, Tae-Hwa
Abstract: Even though tsunami-caused damages mainly refer to ones from inundations and strong currents, recent observations reveal that tsunami waves had significantly affected morphological features in the nearshore area. Since strong and sometimes catastrophic currents are created by tsunami waves, the harbor area is also vulnerable to the morphological changes from tsunami impacts. In this study, the morphological responses to the tsunami waves are examined through numerical simulations using Xbeach model. As a real-scale implementation, 2011 Tohoku-oki tsunami, one of the most destructive tsunamis in history is attempted with a focus on the localized effects of tsunami waves on sedimentation at the Crescent City Harbor. The tsunami physics are known to be less predictable in the nearshore area because of the complex geometric features and the existence of various types of turbulence sources, it is much important to recreate tsunami current field more accurately for the sediment calculations. To this end, a multi-grids and multi-physics tsunami model is preferred for the better reproduction of current fields by tsunami waves in the nearshore. Results on velocity fields computed by tsunami model show that strong and catastrophic currents with large coherent structures were induced by tsunami waves in the harbor area(Son and Lynett, 2015). Such pre-calculated wave fields during tsunami events are then input to Xbeach model to simulate sedimentation process in the area of interest. Bathymetric changes predicted by Xbeach model reveal that strong velocity fields which had been successfully generated through the tsunami model resulted severe sedimentation processes of scouring and deposition which is consistent with the observation.